2017
DOI: 10.4103/0970-2113.201300
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Aspergillus hypersensitivity and allergic bronchopulmonary aspergillosis in patients with bronchial asthma at a tertiary care center in North India

Abstract: Background:The prevalence of Aspergillus hypersensitivity (AH) and allergic bronchopulmonary aspergillosis (ABPA) has been variably reported. Systematic data regarding Aspergillus sensitization and ABPA are lacking from this part of the country.Objectives:The aim of this study was to evaluate the prevalence of AH and ABPA in Uttar Pradesh.Setting and Design:This was prospective observational study. All patients attending outpatient Department of Pulmonary Medicine of our institute were included in the study.Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…In a study performed by Maurya et al (22), 10.4% of asthmatic patients had positive reaction to Aspergillus - specific IgG. However, in the present study, the level of Aspergillus - specific IgG was 43.0% in patients with asthma.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In a study performed by Maurya et al (22), 10.4% of asthmatic patients had positive reaction to Aspergillus - specific IgG. However, in the present study, the level of Aspergillus - specific IgG was 43.0% in patients with asthma.…”
Section: Discussioncontrasting
confidence: 76%
“…In several studies, the positive reaction rates to AST were reported as 21.5% (20), 27.6% (21), and 35.1% (22). Moreover, the levels of total IgE in the current study were low, compared to the results reported by the previous studies (19, 22). The obtained differences in positive rates may be due to varieties in genetic, nationality, race, and geographical and climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…wherein the incidence of ABPA in asthma clinic was found to be 21.7%. [ 10 ] In patients with asthma, bronchiectasis involving three or more lobes, presence of centrilobular nodules, and mucoid impaction highly suggest the possibility of ABPA. [ 8 ] In our study, 64.6% of the patient had bronchiectasis with or without other lung findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 57 patients with severe acute asthma admitted to an intensive care unit, the prevalence of ABPA was found to be 39 per cent (compared to 21% in the outpatient asthma group) 20 . The prevalence of ABPA complicating asthma reported in the last decade is summarized in Table I 21 22 23 24 25 26 27 28 29 30 31 32 . The data suggest a high prevalence of AS and ABPA in special clinics ( Table I ) and a higher prevalence in India compared to other countries.…”
Section: Epidemiology Of Abpamentioning
confidence: 99%